Analisis Pengaruh CAR, NPF, FDR, BOPO dan Inflasi terhadap Profitabilitas Perbankan Syariah di Indonesia: Studi Masa Pandemi Covid-19 - Rofiul Wahyudi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
Corona Virus Desease 19 (Covid-19) is a pandemic that has spread to almost all countries, including Indonesia. As a result, impacts to various types of sectors are not only health, but also the banking system. The purpose of this study to analyze the CAR, NPF, FDR, ROA and inflation on the profitability of Islamic banking days of the pandemic Covid-19. This research method is quantitative descriptive using secondary data for the first quarter of 2020 obtained from the official pages of each bank and inflation data from the Central Statistics Agency (BPS) page. Purposive sampling selected in this study were that the total sample of 11 Islamic Banks. Statistical test results show simultaneously CAR, FDR, NPF, BOPO and Inflation have an impact on ROA even during the Covid-19 pandemic. This finding has practical implications for customers that make it possible to continue using Islamic banking services.